Popular political continuity in urban England, 1867-1918: the case studies of Bristol and Northampton - Kidd, Matthew (2016)
This thesis examines the transition between working-class radicalism and labour politics in two provincial English constituencies, Bristol and Northampton, between 1867 and 1918. By combining local case studies with a textual analysis of empirical material and a conceptual approach to ideology, it offers fresh insights into popular political change in late nineteenth- and early twentieth-century Britain.